Target Identification of Active Constituents of Shen Qi Wan to Treat Kidney Yang Deficiency Using Computational Target Fishing and Network Pharmacology - Zhang, Jie Ying; Hong, Chun Lan; Chen, Hong Shu; Zhou, Xiao Jie; Zhang, Yu Jia; Efferth, Thomas; Yang, Yuan Xiao; Li, Chang Yu (Frontiers in Pharmacology, 2019)
Background: Kidney yang deficiency syndrome (KYDS) is one of the most common syndromes treated with traditional Chinese medicine (TCM) among elderly patients. Shen Qi Wan (SQW) has been effectively used in treating various diseases associated with KYDS for hundreds of years. However, due to the complex composition of SQW, the mechanism of action remains unknown. Purpose: To identify the mechanism of the SQW in the treatment of KYDS and determine the molecular targets of SQW. Methods: The potential targets of active ingredients in SQW were predicted using PharmMapper. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses using the Molecule Annotation System (MAS3.0). The protein-protein interaction (PPI) network of these potential targets and “Components-Targets-Pathways” interaction networks were constructed using Cytoscape. We also established a KYDS rat model induced by adenine to investigate the therapeutic effects of SQW. Body weight, rectal temperature, holding power, water intake, urinary output, blood urea nitrogen (BUN), serum creatinine (Scr), adrenocorticotrophic hormone (ACTH), cortisol (CORT), urine total protein (U-TP) and 17-hydroxy-corticosteroid (17-OHCS) were measured. Additionally, the mRNA expression levels of candidates were detected by qPCR. Results: KYDS-caused changes in body weight, rectal temperature, holding power, water intake, urinary output, BUN, Scr, ACTH, CORT, U-TP and 17-OHCS were corrected to the baseline values after SQW treatment. We selected the top 10 targets of each component and obtained 79 potential targets, which were mainly enriched in the proteolysis, protein binding, transferase activity, T cell receptor signaling pathway and focal adhesion. SRC, MAPK14, HRAS, HSP90AA1, F2, LCK, CDK2 and MMP9 were identified as targets of SQW in the treatment of KYDS. The administration of SQW significantly suppressed the expression of SRC, HSP90AA1, LCK and CDK2 and markedly increased the expression of MAPK14, MMP9 and F2. However, HRAS levels remained unchanged. Conclusion: These findings demonstrated that SQW corrected hypothalamic–pituitary–target gland axis disorder in rats caused by KYDS. SRC, MAPK14, HRAS, HSP90AA1, F2, LCK, CDK2 and MMP9 were determined to the therapeutic target for the further investigation of SQW to ameliorate KYDS.